Effect of Electroacupuncture on Knee Osteoarthritis: a Systematic Review - Jie LIN; Changlong FU; Li LI; Mingxia WU (康复学报)
Objective:To provide a reliable evidence-based evidence for clinical application of electroacupuncture (EA) on knee osteoarthritis, a systematic review was conducted.Methods:A literature search was performed in databases including Pubmed, CNKI, VIP and Wan Fang with"knee osteoarthritis""electroacupuncture"which were selected as keywords to obtain the original research articles. The articles published before December 31, 2015. The evaluation tool of bias risk was applied for quality assessment of eligible studies. The software of Review Manager 5.3 was used for qualitative analysis of literatures and meta-analysis.Results:A total of 28 studies were included. Compared with the Western medicine group, the Western Ontario and McMaster University (WOMAC) score in the EA group was decreased (MD=-5.41, P<0.01), the Lequesne score was decreased (MD=-1.79, P<0.01), the LKSS score was increased (MD=9.00, P<0.01) and the VAS score was reduce (MD=-0.39, P=0.30).Conclusion:Existing evidence suggested that EA could effectively relieve pain and improve symptoms of knee osteoarthritis in patients. However, larger-scale well-designed trials are needed to confirm the curative effect of EA.